2014
DOI: 10.1016/j.mjafi.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic breast surgery: Initial experience in an Oncology Center

Abstract: Oncoplastic breast surgery combines the principles of surgical oncology with those of plastic and reconstructive surgery and our initial experience shows that OBS leads to aesthetically pleasing and oncologically sound results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Superior pedicle reduction mammaplasty, the inferior pedicle reduction mammaplasty, round block mastopexy, Grisotti technique and LD flap are some oncoplasty surgery options for these tumours. [11][12][13][14] Our comparative study showed the clear advantage of oncoplastic surgery compared to conventional BCS in terms of the volume of the resected breast specimen, the width of the cut margin obtained and the frequency of clear margins obtained. Critics may argue that wider glandular excisions in OBS procedures are necessary to achieve symmetry with the contralateral breast and not necessarily to obtain wider surgical margins.…”
Section: Discussionmentioning
confidence: 70%
“…Superior pedicle reduction mammaplasty, the inferior pedicle reduction mammaplasty, round block mastopexy, Grisotti technique and LD flap are some oncoplasty surgery options for these tumours. [11][12][13][14] Our comparative study showed the clear advantage of oncoplastic surgery compared to conventional BCS in terms of the volume of the resected breast specimen, the width of the cut margin obtained and the frequency of clear margins obtained. Critics may argue that wider glandular excisions in OBS procedures are necessary to achieve symmetry with the contralateral breast and not necessarily to obtain wider surgical margins.…”
Section: Discussionmentioning
confidence: 70%
“…As the survival for breast cancer patients continues to improve, the future of surgery for breast cancer lies in integrating the principles of OPS into our practice as the focus of care shifts to improving QOL. Several Indian authors[ 20 21 22 ] have reported case series on the safety and esthetic outcome of oncoplastic procedures. The risk factors reported for poor cosmetic outcome were age, volume of breast tissue excised, and estimated percentage of breast volume excised ( P < 0.05).…”
Section: Surgical Advances: Indian Experiencementioning
confidence: 99%
“…Oncoplastic surgery (OPS) of the breast includes tumour‐specific immediate reconstruction, which can be defined as breast cancer surgery with immediate reconstruction in cases of partial and total mastectomy . However, a systematic categorization of breast surgeries is lacking despite the fact that numerous new surgical and oncoplastic techniques have been reported …”
Section: Introductionmentioning
confidence: 99%